2019
DOI: 10.2147/cmar.s215427
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Integrative gene expression profiling reveals that dysregulated triple microRNAs confer paclitaxel resistance in non-small cell lung cancer via co-targeting MAPT</p>

Abstract: Background Paclitaxel has shown significant anti-tumor activity against non-small cell lung cancer (NSCLC); however, resistance to paclitaxel frequently occurs and represents a significant clinical problem and its underlying molecular mechanism remains elusive. Methods Long-term treatment of culture cell with paclitaxel was carried out to mimic the development of acquired drug resistance in NSCLC. Cell proliferation and clonogenic assay and apoptosis evaluation were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A simple search of common miRNA target site prediction programs (e.g., targetscan.org) reveals several conserved binding sites within the tau 3 â€Č UTR. Consistent with this, a handful of miRNAs have been shown to bind to tau mRNA, including miR-132 (19,20), miR-34 (11), miR-186 (21), miR-219 (22), miR-362 (23), and miR-766 (23). Most groups have relied on 3 â€Č UTR luciferase reporter assays and mutagenesis to confirm gene expression regulation in vitro.…”
Section: Perspective Article Evidence That Tau Is a Microrna Targetmentioning
confidence: 85%
“…A simple search of common miRNA target site prediction programs (e.g., targetscan.org) reveals several conserved binding sites within the tau 3 â€Č UTR. Consistent with this, a handful of miRNAs have been shown to bind to tau mRNA, including miR-132 (19,20), miR-34 (11), miR-186 (21), miR-219 (22), miR-362 (23), and miR-766 (23). Most groups have relied on 3 â€Č UTR luciferase reporter assays and mutagenesis to confirm gene expression regulation in vitro.…”
Section: Perspective Article Evidence That Tau Is a Microrna Targetmentioning
confidence: 85%
“…The spearman correlation was used to calculate the correlation of GJB2 or SCNN1B and drug target genes, and those with p < 0.05 were selected as interest genes. Moreover, the drug-sensitive or drug-resistant genes in interest genes were identified from the literatures with key words of 19 drugs (shown in supplementary Table S2 [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]). The interaction network of GJB2 or SCNN1B with target genes and drugs were constructed and visualized by Cytoscape v.3.5.…”
Section: Discussionmentioning
confidence: 99%
“…MAPT can also determine paclitaxel chemosensitivity by interacting with several miRNAs in gastric cancer and non-small cell lung cancer [37]. Moreover, clinical and in vitro studies have demonstrated that the expression level of MAPT is positively associated with ER expression, and is influenced by ER signaling [38,39].…”
Section: Discussionmentioning
confidence: 99%